Dampak Pembangunan Pasar Modern (Alfamart dan Indomaret) terhadap Pasar Tradisional (Warung Serba Ada) Kota Pekanbaru - Nurmasari; Al Hafis, Raden Imam; Butarbutar, Josua (Asketik: Jurnal Agama dan Perubahan Sosial, 2019)
This research is a study related to the impact of modern market growth (Alfamart and Indomaret) on traditional markets (department stores) in the city of Pekanbaru. The theories and framework used in this research are the concepts of development while the research method used is a qualitative approach delivered by John W. Creswell. Because of it, the expected results will be more comprehensive about the impact of the existence of the modern market on traditional ones (waserda). Meanwhile, the objectives of this study are 1. Consistency of the government of Pekanbaru City on the Implementation of Regulation Number 9, 2014. 2. Perception of traditional market traders on the existence of modern markets. 3. The impact of the existence of a modern retail market (Alfamart and Indomaret) on the business of traditional traders of all-around stalls (waserda). 4. Efforts made by traditional market traders (waserda) to maintain the existence of their businesses. From the results obtained in this research, it is expected to be able to provide input and advice to the community, government, and private sector on the impact of the existence of modern markets on traditional ones, and to make appropriate formulations in dealing with problems that occur. So that in the end modern markets and traditional ones can grow and develop together and complement each other in Pekanbaru City. Waserda, ritel modern, alfamart, indomaret.